Porous membranes in secondary battery technologies. (13th March 2017) - Lu, Wenjing; Yuan, Zhizhang; Zhao, Yuyue; Zhang, Hongzhang; Zhang, Huamin; Li, Xianfeng
Abstract : The research and development of porous membranes for secondary battery technologies were reviewed and summarized. Abstract : Secondary batteries have received huge attention due to their attractive features in applications of large-scale energy storage and portable electronic devices, as well as electrical vehicles. In a secondary battery, a membrane plays the role of separating the anode and cathode to prevent the occurrence of a short circuit, while allowing the transport of charge carriers to achieve a complete circuit. The properties of a membrane will largely determine the performance of a battery. In this article, we review the research and development progress of porous membranes in secondary battery technologies, such as lithium-based batteries together with flow batteries. The preparation methods as well as the required properties of porous membranes in different secondary battery technologies will be elucidated thoroughly and deeply. Most importantly, this review will mainly focus on the optimization and modification of porous membranes in different secondary battery systems. And various modifications on commercial porous membranes along with novel membrane materials are widely discussed and summarized. This review will help to optimize the membrane material for different secondary batteries, and favor the understanding of the preparation–structure–performance relationship of porous membranes in different secondary batteries. Therefore, this review will provide an extensive, comprehensive and professional reference to design and construct high-performance porous membranes.